2016
DOI: 10.1109/jbhi.2015.2490087
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Simulated Vocal Dysfunctions Using Complex sEMG Patterns

Abstract: Symptoms of voice disorder may range from slight hoarseness to complete loss of voice; from modest vocal effort to uncomfortable neck pain. But even minor symptoms may still impact personal and especially professional lives. While early detection and diagnosis can ameliorate that effect, to date, we are still largely missing reliable and valid data to help us better screen for voice disorders. In our previous study, we started to address this gap in research by introducing an ambulatory voice monitoring system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…At present, a series of physiological mechanisms specific to the laryngeal and paralaryngeal areas are reported to be associated with increased vocal effort, including increased intrinsic laryngeal tension, extrinsic laryngeal tension, supraglottal compression, and subglottal pressure. All of these mechanisms have been reported to increase when vocally healthy speakers purposefully increase effort and strain (Lien, Michener, Eadie, & Stepp, 2015;McKenna, Murray, Lien, & Stepp, 2016;Rosenthal, Lowell, & Colton, 2014; N. R. Smith et al, 2016) and are reported in speakers with voice disorders characterized by symptoms of excessive vocal effort (e.g., vocal hyperfunction).…”
Section: Proposed Physiological Mechanisms Of Vocal Effortmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, a series of physiological mechanisms specific to the laryngeal and paralaryngeal areas are reported to be associated with increased vocal effort, including increased intrinsic laryngeal tension, extrinsic laryngeal tension, supraglottal compression, and subglottal pressure. All of these mechanisms have been reported to increase when vocally healthy speakers purposefully increase effort and strain (Lien, Michener, Eadie, & Stepp, 2015;McKenna, Murray, Lien, & Stepp, 2016;Rosenthal, Lowell, & Colton, 2014; N. R. Smith et al, 2016) and are reported in speakers with voice disorders characterized by symptoms of excessive vocal effort (e.g., vocal hyperfunction).…”
Section: Proposed Physiological Mechanisms Of Vocal Effortmentioning
confidence: 99%
“…It follows that excessive extrinsic laryngeal muscle tension has been identified as a clinical marker of voice disorders (Angsuwarangsee & Morrison, 2002) and has been targeted diagnostically and therapeutically (e.g., laryngeal palpation, circumlaryngeal massage; Roy, Ford, & Bless, 1996;Roy & Leeper, 1993). Yet, studies seeking to quantitatively evaluate extrinsic laryngeal muscle activation patterns as a means for discriminating between voice types and health status (i.e., healthy speakers vs. those with voice disorders) have yielded conflicting results (Redenbaugh & Reich, 1989; N. R. Smith et al, 2016;Stepp, Heaton, Jette, Burns, & Hillman, 2010;Stepp et al, 2011;Van Houtte, Claeys, D'Haeseleer, Wuyts, & Van Lierde, 2013).…”
Section: Proposed Physiological Mechanisms Of Vocal Effortmentioning
confidence: 99%
“…55 More recent work extended the information gained from the voice sensors to predict subglottal pressures, 56 aerodynamic patterns, 57 and muscle activation patterns associated with normal and abnormal voicing. 52,58,59 In the near future, these devices could be purchased by consumers as disposable sensors that communicate with smartphones to record voice use patterns and eventually provide biofeedback to the user regarding their accuracy in implementing targeted therapeutic voice use patterns in daily life. 53 Recent use of smartphones to facilitate accuracy and adherence to voice therapy methods also shows promise for future implementation of media that can be used by clinicians to ensure consistent and accurate patient practice of voice therapy methods.…”
Section: Diagnosis Using Patient-specific Voice Modelingmentioning
confidence: 99%
“…V OICE pathologies arise either due to physical changes in the voice production mechanism (e.g., in the respiratory system, vocal folds, and vocal tract) [1], [2] or due to improper vocal use when the physical structure of the mechanism is normal (e.g., vocal fatigue or ventricular phonation) [3]- [5]. Examples of voice pathologies are dysarthria [7], dysphonia [8], vocal polyp [9], and developmental dysphasia [13].…”
Section: Introductionmentioning
confidence: 99%